Between- and within-subject associations of PTSD symptom clusters and marital functioning in military couples - Allen, Elizabeth; Knopp, Kayla; Rhoades, Galena; Stanley, Scott; Markman, Howard (Journal of family psychology, 2018)
Using data from 570 male service members and their wives, the current study investigated over-time associations between male service members' self-report of posttraumatic stress disorder (PTSD) symptoms and marital functioning (marital satisfaction, positive bonding, conflict behavior) as perceived by both spouses. Analyses spanned 5 time points over a 2-year period and fully disentangled between- and within-subject effects. Higher levels of all four PTSD symptom clusters (numbing, hyperarousal, effortful avoidance, and reexperiencing) showed significant between-subject associations with lower levels of marital satisfaction and positive bonding, and higher levels of conflict for both men and women, whereas there were markedly fewer significant within-subject associations. When running models with all four PTSD symptom clusters entered at once, the primary between-subject finding was that men with higher numbing symptoms overall reported poorer marital functioning in all domains; there were no significant between-subject links between numbing and marital functioning for women. In contrast, within-subject effects for numbing were found for both men and women, linking increased numbing with decreased positive bonding and increased conflict behavior over time; women also had lower marital satisfaction when their husbands reported relatively higher numbing. Between-subject analyses also revealed that for men with higher average levels of effortful avoidance, wives reported lower levels of satisfaction and positive bonding, whereas men themselves reported less frequent conflict behavior. Finally, within-subject effects showed that at times when men reported increased hyperarousal, they also perceived increased marital conflict, whereas women surprisingly reported increased marital satisfaction. Implications of divergent between- and within-subject results are discussed. (PsycINFO Database Record